(Mis)Representing Weight and Obesity in the British Press Fear, Divisiveness, Shame and Stigma - Coltman-Patel, Tara. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book is a linguistic analysis of the British obesity media narrative, analysing a large corpus of published newspaper articles to demonstrate how the language used perpetuates common misconceptions and stereotypes about weight and obesity, and then exploring the sociological effects of these widespread conceptualisations. Weight stigma and weight bias are misunderstood issues, and often underestimated in terms of their prevalence and effect by society at large. The author examines topics including the role of power and persuasion, the use of metaphor, the personal stories of members of the general public, and the gendered real-life consequences of arbitrary weight standards to provide a linguistic driven study of obesity in news media. Obesity is an issue which sits at the intersection of science and the humanities, and as such, although the research methods used are firmly situated within the field of Linguistics, this book will also be of interest to readers from fields as diverse as Sociology, Fat Studies, Media Studies, Medicine and Psychology. Tara Coltman-Patel is a Senior Research Associate in the Department of Linguistics and English Language at Lancaster University, UK. .
1. Introduction: Weight Stigma, News Media and This Research -- 2. Fear: Expert Voices and the (Mis)Representation of Science and Health -- 3. Divisiveness: The Metaphorical Conceptualisation of Obesity -- 4. Shame: Challenging Linguistic Strategies of Representation -- 5. Conclusion .
Keywords: Linguistics -- Methodology; Human body -- Social aspects; Journalism; Health; Sex; Knowledge, Sociology of; Sociolinguistics; Research Methods in Language and Linguistics; Sociology of the Body; News Journalism; Gender and Health; Sociology of Knowledge and Discourse; Sociolinguistics